U.S. Science and Engineering Workforce: Underrepresentation of Women and Minorities. (May 2018) - Varma, Roli
Increasingly, industrial leaders, governmental officials, and academic scholars have become concerned whether the United States can successfully compete in science and engineering (S&E) fields. This is when employment in S&E jobs has grown faster than employment in all occupations in the United States. It is proposed that the United States has not been able to build its S&E human capital necessary for technological innovations and economic growth. Women and minorities are seen as essential to fill the perceived gap. There is a higher representation of women in S&E education and occupations. Yet overall demographics of S&E fields have remained unchanged. The U.S. technology industry has been progressively employing workers from foreign countries to meet their S&E internal workforce needs. Many have been outsourcing the work to developing countries, namely China and India. This article shows that technology companies that embrace the United States's changing demographics would gain the economic benefits from a diverse S&E workforce.